2019
DOI: 10.1016/j.ces.2018.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of fractal-tree-like heat exchanger manufactured by 3D printing

Abstract: The manufacturing difficulties of complex fractal-tree-like heat exchangers have limited their industrial applications, although many evidences have shown that they have significant advantages in heat transfer. Nevertheless, the emerging 3D printing technology has brought great opportunity for the development of complex structured device. In the present study, three-dimensional (3D) fractal-tree-like heat exchangers were designed and manufactured using 3D printing technology. Their performance was evaluated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…The scale, shape and application tend to be diversified. Furthermore, the fractaltree-like structure characteristics mainly include the branch number and angle [18], the channel aspect ratio [19], layer number [20] and shape [21][22][23], which can affect the fractal heat exchanger performance. The bifurcate structure of the vascular or tracheal system in animals; Fractal-like branching channel flow networks: (c1) The fractal-tree-like microchannel network [19], (c2) The overall shape of 5-layer fractal-tree-like microchannel [20], (c3) The tree-shaped microchannel heat sink with cavities [21], (c4) The tree-shaped microchannel heat sink with cavities [21]; (d1) The CAD diagram of Y-type heat exchanger [22], (d2) The CAD diagram of H-type heat exchanger [22], (d3) The plate heat exchanger with lung pattern [23].…”
Section: Fractal-tree-like Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The scale, shape and application tend to be diversified. Furthermore, the fractaltree-like structure characteristics mainly include the branch number and angle [18], the channel aspect ratio [19], layer number [20] and shape [21][22][23], which can affect the fractal heat exchanger performance. The bifurcate structure of the vascular or tracheal system in animals; Fractal-like branching channel flow networks: (c1) The fractal-tree-like microchannel network [19], (c2) The overall shape of 5-layer fractal-tree-like microchannel [20], (c3) The tree-shaped microchannel heat sink with cavities [21], (c4) The tree-shaped microchannel heat sink with cavities [21]; (d1) The CAD diagram of Y-type heat exchanger [22], (d2) The CAD diagram of H-type heat exchanger [22], (d3) The plate heat exchanger with lung pattern [23].…”
Section: Fractal-tree-like Structurementioning
confidence: 99%
“…Furthermore, the fractaltree-like structure characteristics mainly include the branch number and angle [18], the channel aspect ratio [19], layer number [20] and shape [21][22][23], which can affect the fractal heat exchanger performance. The bifurcate structure of the vascular or tracheal system in animals; Fractal-like branching channel flow networks: (c1) The fractal-tree-like microchannel network [19], (c2) The overall shape of 5-layer fractal-tree-like microchannel [20], (c3) The tree-shaped microchannel heat sink with cavities [21], (c4) The tree-shaped microchannel heat sink with cavities [21]; (d1) The CAD diagram of Y-type heat exchanger [22], (d2) The CAD diagram of H-type heat exchanger [22], (d3) The plate heat exchanger with lung pattern [23]. Fractal-like branching channel flow networks: (c1) The fractal-tree-like microchannel network [19], (c2) The overall shape of 5-layer fractal-tree-like microchannel [20], (c3) The tree-shaped microchannel heat sink with cavities [21], (c4) The tree-shaped microchannel heat sink with cavities [21]; (d1) The CAD diagram of Y-type heat exchanger [22], (d2) The CAD diagram of H-type heat exchanger [22], (d3) The plate heat exchanger with lung pattern [23].…”
Section: Fractal-tree-like Structurementioning
confidence: 99%
“…Sun et al investigated the flow and heat transfer of tree‐like minichannel heat sink by CFD software and obtained the small pressure drop and excellent temperature uniformity. Wang et al designed two fractal tree‐like heat sinks and studied their hydrodynamic and thermal characteristics by experiment and simulation. Their results emphasized the superiority of comprehensive performance of the proposed heat sinks over the traditional spiral tube sinks.…”
Section: Introductionmentioning
confidence: 99%
“…Many comparisons between the tree-like network heat sink and different traditional structural exchangers were performed. Wang et al [3] applied 3D printing technology in Manufacturing tree-like network heat exchanger and compared it with traditional spiral-tube exchangers in the performance of heat transfer and flow. Numerically and experimentally, the results showed that the structure of fractal-tree-like can reduce more pressure drop and have a higher value of coefficient of performance.…”
Section: Introductionmentioning
confidence: 99%